Attitudes toward adolescent self‐harm and its prevention: The views of those who self‐harm and their peers. Issue 3 (20th February 2018) - Doyle, Louise
Abstract: Problem: Adolescent self‐harm is a common phenomenon; however, little is known about young peoples' attitudes toward self‐harm and what they believe can be done to prevent it. This study aimed to identify adolescents' attitudes about self‐harm and their perspectives on preventing it. Methods: A cross‐sectional anonymous survey was administered to 856 post‐primary school students across 11 schools in Dublin, Ireland. Attitudes toward self‐harm were captured through a five‐item scale and views on prevention of self‐harm were captured through an open‐ended survey question. Responses from those who self‐harmed and those who did not were compared to identify differences. Findings: Significant differences were identified between those who self‐harmed and their peers. Those who self‐harmed were less likely to believe that self‐harm was carried out to get attention or was a result of loneliness or depression; they were more likely to believe that self‐harm was impulsive. Findings demonstrated that a majority of young people believed that self‐harm could be prevented and a number of preventative strategies were identified. Conclusions: It is important that the views of adolescents are incorporated into the design and delivery of youth‐friendly services and that there is a focus on increasing awareness of the youth‐orientated services that currently exist.